An Algebraic Trigonometry!

Geometry Level 4

{ tan ( x ) + tan ( y ) + tan ( z ) = 6 ( cot ( x ) + cot ( y ) + cot ( z ) ) tan 2 ( x ) + tan 2 ( y ) + tan 2 ( z ) = 6 ( cot 2 ( x ) + cot 2 ( y ) + cot 2 ( z ) ) tan 3 ( x ) + tan 3 ( y ) + tan 3 ( z ) = 6 ( cot 3 ( x ) + cot 3 ( y ) + cot 3 ( z ) ) \begin{cases} \tan(x)+\tan(y)+\tan(z)= 6-(\cot(x)+\cot(y)+\cot(z)) \\ \tan^2(x)+\tan^2(y)+\tan^2(z)= 6-(\cot^2(x)+\cot^2(y)+\cot^2(z) ) \\ \tan^3(x)+\tan^3(y)+\tan^3(z)= 6-(\cot^3(x)+\cot^3(y)+\cot^3(z) ) \\ \end{cases}

If x , y x,y and z z are real numbers that satisfy the three equations above. Find the value of the expression below.

tan ( x ) tan ( y ) + tan ( y ) tan ( z ) + tan ( z ) tan ( x ) + 3 tan ( x ) tan ( y ) tan ( z ) \left \lfloor \frac{\tan(x)}{\tan(y)} + \frac{\tan(y)}{\tan(z)} + \frac{\tan(z)}{\tan(x)} + 3\tan(x) \tan(y) \tan(z) \right \rfloor


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Shivamani Patil
Jul 14, 2015

Let tan x = a , tan y = b , tan z = c \tan { x } =a,\tan { y } =b,\tan { z } =c .

Given system is equal to

a + b + c = 6 1 a 1 b 1 c a+b+c=6-\frac { 1 }{ a } -\frac { 1 }{ b } -\frac { 1 }{ c }

a 2 + b 2 + c 2 = 6 1 a 2 1 b 2 1 c 2 { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }=6-\frac { 1 }{ { a }^{ 2 } } -\frac { 1 }{ { b }^{ 2 } } -\frac { 1 }{ { c }^{ 2 } }

a 3 + b 3 + c 3 = 6 1 a 3 1 b 3 1 c 3 { a }^{ 3 }+{ b }^{ 3 }+{ c }^{ 3 }=6-\frac { 1 }{ { a }^{ 3 } } -\frac { 1 }{ { b }^{ 3 } } -\frac { 1 }{ { c }^{ 3 } } .

From second equation we complete squares to obtain

( a 1 a ) 2 + ( b 1 b ) 2 + ( c 1 c ) 2 = 0 { \left( a-\frac { 1 }{ a } \right) }^{ 2 }+{ \left( b-\frac { 1 }{ b } \right) }^{ 2 }+{ \left( c-\frac { 1 }{ c } \right) }^{ 2 }=0

a = b = c = ± 1 \Rightarrow a=b=c=\pm 1 .

Now rearranging 3rd equation and adding 3 3 time first equation we get

a 3 + b 3 + c 3 + 1 a 3 + 1 b 3 + 1 c 3 + 3 ( a + 1 a + b + 1 b + c + 1 c ) = 6 + 18 { a }^{ 3 }+{ b }^{ 3 }+{ c }^{ 3 }+\frac { 1 }{ { a }^{ 3 } } +\frac { 1 }{ { b }^{ 3 } } +\frac { 1 }{ { c }^{ 3 } } +3\left( a+\frac { 1 }{ a } +b+\frac { 1 }{ b } +c+\frac { 1 }{ c } \right) =6+18

( a + 1 a ) 3 + ( b + 1 b ) 3 + ( c + 1 c ) 3 = 24 { \left( a+\frac { 1 }{ a } \right) }^{ 3 }+{ \left( b+\frac { 1 }{ b } \right) }^{ 3 }+{ \left( c+\frac { 1 }{ c } \right) }^{ 3 }=24

Therefore a = b = c = 1 \boxed {a=b=c=1} .

Elegant! Nicely Done.

Satyajit Mohanty - 5 years, 11 months ago

Log in to reply

Thank you.

shivamani patil - 5 years, 11 months ago
Satyajit Mohanty
Jul 9, 2015

Aakash Khandelwal
Jul 11, 2015

Make tan and cot trigonometric ratios with same #arguments in all 3 equations .

Sum and reciprocal of a no May have only 2 or as -2 as their sum.

Hence all tan's or cot's =+-1

But tanx=-1will not be satisfied

Hence tanx=1 answer indeed =6

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...